Princípios organizadores e núcleo central das representações sociais. Hipóteses empíricas - Patrick Rateau (Arquivos Brasileiros de Psicologia, 2014)
This article aims at studying a possible articulation between the theory of the central core of social representations and the theory of the organizing principles. The confrontation of the results of three research undertaken in connection with the social representation of the studies (two already published and one original) in three distinct populations indicates deep differences in terms of core between these populations but an important transversality of the organizing principles of the standpoints. The assumption thus is put forth that the organizing principles constitute the common base of diversified standpoints according to the social position of the groups and that, among these standpoints, some are the object of strong consensus inside the groups and thus constitute the central system of their representation. This assumption implies that common organizing principles could report different representations in terms of central system.